2022
DOI: 10.1002/jgm.3459
|View full text |Cite
|
Sign up to set email alerts
|

Circulating plasma miR222‐3P status and its potential diagnostic performance in prostate cancer

Abstract: Background: Although studies suggest that miR222-3p is dysregulated in prostate cancer (PC) cells and tissues, the possible changes in the level of miR222-3p in the plasma samples of PC patients remained unclear. The present study aimed to evaluate the diagnostic value of the plasma miR222-3p expression level as a potential biomarker in PC, benign prostatic hyperplasia (BPH) and healthy people.Methods: Blood samples were collected from 100 adult males (54 patients with PC, 27 patients with BPH and 19 healthy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The results of the present study are consistent with them, and patients with low miRNA-222 expression levels were more likely to develop prostate cancer than those with high miRNA-222 expression levels. Zohreh Heydari et al [ 49 ] found in their latest study that miRNA-222 was significantly upregulated in the circulating plasma of prostate cancer patients, but not significantly upregulated in prostate hyperplasia patients. The results of our study are the opposite, possibly because prostate biopsy may affect the expression of miRNA in the peripheral blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are consistent with them, and patients with low miRNA-222 expression levels were more likely to develop prostate cancer than those with high miRNA-222 expression levels. Zohreh Heydari et al [ 49 ] found in their latest study that miRNA-222 was significantly upregulated in the circulating plasma of prostate cancer patients, but not significantly upregulated in prostate hyperplasia patients. The results of our study are the opposite, possibly because prostate biopsy may affect the expression of miRNA in the peripheral blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-222-3p expression in PB is capable of predicting the MPP diagnosis and prognosis from biological perspective, and also serves for prostate cancer detection as a biomarker without invasiveness. 37,38 In this study, based on ROC curve analysis results, miR-222-3p expression in T2DM patients' PB could predict DFU risk as a useful biomarker. In addition, miR-222-3p expression in PB and WMT showed a positive relevance to DFU duration, complete healing time of DFU and a negative relevance to the wound healing rate after eight weeks of treatment.…”
mentioning
confidence: 91%